AN ANALYSIS OF TRANSLATION TECHNIQUES IN INDONESIAN SUBTITLE IN THE MOVIE ENTITLED LUCA - Septi Rahmawati; Pratama , Mochamad Rizqi Adhi (Universitas Ngudi Waluyo, 2024)
Translation is an attempt to transfer meaning, ideas, or information from the source language (SL) to the target language (TL). This research aims to analyze the translation technique of English to Indonesian subtitles in the movie entitled Luca. The theory used in the study was by Molina & Albir (2002) to collect and analyze the data, while the method used in this study was a descriptive qualitative method. The total numbers found 534 and the percentage of each technique are, literal translation occurs 133 times (25%), reduction occurs 75 times (14%), generalization occurs 64 times (12%), established equivalent occurs 46 times (8,61%), linguistic compression occurs 38 times (7,12%), adaptation occurs 34 times (6,37%), modulation occurs 31 times (5,81%), transposition occurs 27 times (5,06%), particularization occurs 22 times (4,12%), borrowing occurs 20 times (3,75%), discursive creation occurs 15 times (2,81%), compensation occurs 12 times (2,25%), variation occurs 7 times (1,31%), linguistic amplification occurs 6 times (1,12%), and amplification occurs 4 times (0,75%). The most dominant translation technique found in the movie Luca is literal translation. Keywords: Movie, Subtitle, Translation Technique